2007
DOI: 10.1097/01.prs.0000287330.94038.63
|View full text |Cite
|
Sign up to set email alerts
|

Restylane and People of Color

Abstract: This study demonstrates that with proper and meticulous injection techniques, patients with Fitzpatrick skin types IV to VI can experience the same benefits of Restylane therapy as their lighter-complected counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 6 publications
1
31
0
1
Order By: Relevance
“…While only a few studies on the use of Restylane for skin of colour are reported, the study by Odunze[16] showed that the use of Restylane in people with darker skin (Type IV to VI) was as safe and effective as in people with fair skin. In addition, the study highlighted the importance of minimizing the number of needle punctures to the skin, in order to limit the risk of hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While only a few studies on the use of Restylane for skin of colour are reported, the study by Odunze[16] showed that the use of Restylane in people with darker skin (Type IV to VI) was as safe and effective as in people with fair skin. In addition, the study highlighted the importance of minimizing the number of needle punctures to the skin, in order to limit the risk of hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…There were subtle points emphasized, such as the use of ice before and during treatment, the use of hydrogen peroxide instead of alcohol to clean the skin and pre-treating darker skin with skin bleaching agents. [16]…”
Section: Discussionmentioning
confidence: 99%
“…No transient or permanent adverse events were reported among patients with Fitzpatrick skin types IV through VI. 47 In addition to the three studies described above, five studies included individuals with Fitzpatrick skin . Results from this randomized controlled trial were published in two studies from our review.…”
Section: Outcomes In Subjects With Fitzpatrick Skin Types IV Through Vimentioning
confidence: 99%
“…Subsequent randomized controlled trials have shown that no such effects were seen in the darker skin types and the safety profile is comparable across all skin types. 115,116,117 Serious complications such as vascular occlusion and embolization are very rare but should be carefully considered in order to avoid vision loss and necrosis. Hypersensitivity to filler products is very rare but may lead to angioedema or anaphylaxis.…”
Section: Mental Creasementioning
confidence: 99%